ANALISIS KOMPOSIT HYBRID SERAT KELAPA DAN KULIT JAGUNG TERHADAP KEKUATAN IMPAK SEBAGAI MATERIAL BUMPER - Arif Rochman Fachrudin; Fina Andika Frida Astuti; Agus Dani; Akhmad Hanif Firdaus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Composite is a combination of two or more materials to obtain better combined properties. Composites can be based on natural or synthetic fibers. Natural fiber composites utilize fibers as reinforcement and polymers as a matrix, with the advantages of being light, strong, and environmentally friendly. Hybrid composites combine two or more types of fibers or matrices to combine the advantages of each, resulting in better performance than a single composite. The purpose of this study is to analyze the composite of coconut fiber and corn husk which are natural fibers on the impact strength of the composite as an alternative material for car bumpers. The method used is an experiment with a composite manufacturing process using hand lay up. This study uses a combination of coconut fiber and corn husk fiber with a polyester matrix and MEKPO catalyst. The composition of fiber and matrix is ​​40% fiber and 60% matrix. The results of the study obtained the highest impact strength value of 0.09767 J/mm2 with a volume fraction of 32% Coconut Fiber: 8% Corn Husk Fiber: 60% Polyester Resin. The soaking time of 5% NaOH for 6 hours has the highest impact strength value of 0.09767 J/mm2. The standard bumper has a minimum impact strength of 0.039 J/mm2. The material, soaked for 4 and 6 hours, can be used as an alternative material for car bumpers because it exceeds the standard impact strength..